2018
DOI: 10.5530/pj.2018.4.101
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Cymodocea rotundata Asch. and Schweinf

Abstract: Introduction:Cymodocea rotundata Asch. and Schweinf, a widespread seagrass with reported antimicrobial activity, was investigated for its chemical constituents. Methods: The compounds were isolated by silica gel chromatography and identified by NMR spectroscopy. Results: This study has led to the isolation of β-sitosteryl-3β-glucopyranoside-6′-O-fatty acid esters (1), chlorophyll a (2) and a mixture of β-sitosterol (3a) and stigmasterol (3b) in about 1:1 ratio from the dichloromethane extract of C. rotundata. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…18 Another aspect of our research showed the presence of fatty acids derivatives besides phenolics derivatives, which was detected from GC-MS chromatogram. In a study of 19 has led to the isolation of fatty acid esters, chlorophyll in about 1:1 ratio from the dichloromethane extract of C. rotundata. Fatty acid esters obtained from the extract of C. rotundata exhibited antibacterial activity and partly showed antimicrobial activity B.…”
Section: Fig 8: Exhibition Of Protease Activity By B Cereusmentioning
confidence: 99%
“…18 Another aspect of our research showed the presence of fatty acids derivatives besides phenolics derivatives, which was detected from GC-MS chromatogram. In a study of 19 has led to the isolation of fatty acid esters, chlorophyll in about 1:1 ratio from the dichloromethane extract of C. rotundata. Fatty acid esters obtained from the extract of C. rotundata exhibited antibacterial activity and partly showed antimicrobial activity B.…”
Section: Fig 8: Exhibition Of Protease Activity By B Cereusmentioning
confidence: 99%